The Atlantic walrus : biological, historical, and indigenous insights into species-human interactions - Weber, Xenia Alessandra, 1992-; Olsen, Morton Tange; Jordan, Peter, 1969-; Desjardins, Sean P. A. (Academic Press, 2020)
Addresses the key dimensions of long-term human walrus interactions across the Atlantic Arctic and subarctic regions, over the past millennia. This book brings together research from across the social and natural sciences to explore walrus biology, human culture, environmental conditions and their reciprocal effects. Together, 13 chapters of this book reconstruct the early evolution of walruses, walrus biology, the cultural significance and ecological impact of prehistoric and indigenous hunting practices, as well as the effects of commercial hunting and international trade. This book also examines historic and ongoing management strategies and, the importance of new research methodologies in revealing hitherto unknown details of the past, and concludes by discussing the future for Atlantic walruses in the face of climate change and increased human activities in the Arctic. This volume is an ideal resource for those who are seeking to understand an iconic Arctic species and its long and complex relationship with humans. This includes individuals and researchers with a personal or professional connection to walruses or the Arctic, as well as marine biologists, zoologists, conservationists, paleontologists, archaeologists, anthropologists, historians, indigenous communities, natural resource managers and government agencies. Provides succinct overviews of the biology of the Atlantic Walrus (Odobenus rosmarus rosmarus) as well as human cultures within the North Atlantic Arctic and the surrounding region by consolidating research which until now has been scattered across fields and academic publicationsEditorial team of inter-disciplinary researchers ensuring the breadth, depth and integration of material covered throughout the volumeThirteen chapters, each authored by leading international researchers and experts on the Atlantic WalrusConsiders the inter-relatedness and complexity of species biology, ecological change, human culture, and anthropogenic pressures onto the Atlantic Walrus, all while remaining accessible to readers from different disciplines or a more generalist audienceDraws upon the latest methods in marine mammal and archaeological researchAssesses historical management of the species, while also considering current and future conservation efforts in light of human activities and climate changeText supported by striking and insightful new maps and scientific illustrations, ideal for teaching and outreach